Semiclassical gravitoelectromagnetic inflation in a Lorentz gauge: Seminal inflaton fluctuations and electromagnetic fields from a 5D vacuum state - Membiela, Federico Agustin (2010)
Using a semiclassical approach to Gravitoelectromagnetic Inflation (GEMI), we study the origin and evolution of seminal inflaton and electromagnetic fields in the early inflationary universe from a 5D vacuum state. The difference with other previous works is that in this one we use a Lorentz gauge. Our formalism is naturally not conformal invariant on the effective 4D de Sitter metric, which make possible the super adiabatic amplification of magnetic field modes during the early inflationary epoch of the universe on cosmological scales.